TYPES OF SENTENCES BASED ON THEIR COMMUNICATIVE PURPOSE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the classification of sentences based on theircommunicative purpose, emphasizing the importance of understanding their uniquefunctions in everyday language. The four main sentence types—declarative, interrogative, imperative, and exclamatory—are explained in detail, with examples provided to illustratetheir usage. The article highlights how declarative sentences serve to convey information, interrogative sentences seek answers, imperative sentences provide directions or commands, and exclamatory sentences express strong emotions